Historical Archaeologies of Capitalism - Leone, Mark P (Springer, 2015)
This new edition of Historical Archaeologies of Capitalism shows where the study of capitalism leads archaeologists, scholars and activists. Essays cover a range of geographic, colonial and racist contexts around the Atlantic basin: Latin America and the Caribbean, North America, the North Atlantic, Europe and Africa. Here historical archaeologists use current capitalist theory to show the results of creating social classes, employing racism and beginning and expanding the global processes of resource exploitation. Scholars in this volume also do not avoid the present condition of people, discussing the lasting effects of capitalism’s methods, resistance to them, their archaeology and their point to us now.